Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Pengangguran Terbuka Di Indonesia Periode 1989-2016 - I Imsar (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2018)
This study aims to find out how much influence the inflation, economic growth, and unemployment of the previous period against the level of open unemployment in Indonesia. The research method used is quantitative method with OLS (Ordinary Least Square) method. Data analysis technique using multiple linear regression model supported by classical assumption test. The results showed that the coefficient of determination (R square) of independent variables on the dependent variable is 0.847 or 82.8%. This indicates that the variables Inflation, Economic Growth and Unemployment previous period. can explain the level of Unemployment in Indonesia amounted to 82.8% while the rest 7.2% explained by other factors. From the results of partial significance test variable inflation rate is obtained t count of 0.046996 <2.069 of t table so it can be concluded that the variable that inflation does not significantly affect the unemployment of Indonesia. While for economic growth variable obtained by t count equal to -0.400057 <2,069 from t table so that can be concluded economic growth not significantly affect unemployment in Indonesia. While the previous period unemployment variable obtained t count value of 11.23190> 2.069, it can be concluded that the previous period unemployment significantly affect Indonesia Unemployment. While the results of the simultaneous significance test, then obtained the value of 44.51053> 3.03 and also can be seen in the value of probability is smaller than the level of significance (α) 5% or 0.000000 <0.05 then it can be concluded that Inflation, Economic Growth and Unemployment previous periods simultaneously affect the unemployment rate in Indonesia.